Multistage-responsive nanovehicle to improve tumor penetration for dual-modality imaging-guided photodynamic-immunotherapy. (August 2021) - Feng, Yi; Xie, Xiaoxue; Zhang, Hanxi; Su, Qingqing; Yang, Geng; Wei, Xiaodan; Li, Ningxi; Li, Tingting; Qin, Xiang; Li, Shun; Wu, Chunhui; Zheng, Chuan; et al.
Abstract: The exploration of an intelligent multifunctional imaging-guided therapeutic platform is of great significance because of its ideal delivery efficiency and controlled release. In this work, a tumor microenvironment (TME)-responsive nanocarrier (denoted as MB@MSP) is designed for on-demand, sequentially release of a short D-peptide antagonist of programmed cell death-ligand 1 (named as P D PPA-1) and a photosensitizer methylene blue (MB). Fe3 O4 –Au located in the core of MB@MSP is used as a magnetic resonance imaging and micro-computed tomography imaging contrast agent for noninvasive diagnosis of solid tumors and simultaneous monitoring of drug delivery. The P D PPA-1 coated on MB@MSP can be shed due to the cleavage of the peptide substrate by matrix metalloproteinase-2 (MMP-2) that is highly expressed in the tumor stroma, and disulfide bonding is further broken when it encounters high levels of glutathione (GSH) in TME, which finally leads to significant size reduction and charge-reversal. These transitions facilitate penetration and uptake of nanocarriers against tumors. Noticeably, the released P D PPA-1 can block the immune checkpoint to create an environment that favors the activation of cytotoxic T lymphocytes and augment the antitumor immune response elicited by photodynamic therapy, thus significantly improving therapeutic outcomes. Studies of the underlying mechanisms suggest that the designed MMP-2 and GSH-sensitive delivery system not only induce apoptosis of tumor cells but also modulate the immunosuppressive tumor microenvironment to eventually augment the suppression tumor metastasis effect of CD8 + cytotoxic T cells. Overall, the visualization of the therapeutic processes with comprehensive information renders MB@MSP an intriguing platform to realize the combined treatment of metastatic tumors.